Integrating Conductivity, Immobility, and Catalytic Ability into High‐N Carbon/Graphene Sheets as an Effective Sulfur Host. Issue 7 (26th December 2019) - Xu, Huifang; Jiang, Qingbin; Zhang, Bingkai; Chen, Chao; Lin, Zhan
Abstract: Lithium–sulfur (Li–S) batteries are considered to be one of the most promising candidate systems for next‐generation electrochemical energy storage. The major challenge of this system is the polysulfide shuttle, which results in poor cycling efficiency. In this work, a highly N‐doped carbon/graphene (NC/G) sheet is designed as a sulfur host, which combines the merits of abundant N active sites and high electrical conductivity to achieve in situ anchoring–conversion of lithium polysulfides (LiPSs). Such a host not only has strong binding with LiPSs but also promotes redox kinetics, which are revealed by both experimental investigations and theoretical studies. The sulfur cathode based on the NC/G host exhibits a high initial capacity of 1380 mA h g −1 and a superior cycle stability with a low capacity decay of 0.037% per cycle within 500 cycles at 2 C. Steady areal capacity with a high sulfur loading (5.6 mg cm −2 ) is also attained even without the addition of LiNO3 in the electrolyte. This work proposes and illustrates the importance of in situ anchoring–conversion of LiPSs, offering a new strategy to design multifunctional sulfur hosts for high‐performance Li–S batteries. Abstract : A highly N‐doped carbon/graphene host combines the merits of being attractively conductive, which accelerates efficient electron transfer, having sufficient binding affinity, which renders effective anchoring, and having abundant reactive sites with effective catalytic effects that facilitate redox kinetics to accomplish in situ anchoring–conversion of lithium polysulfides (LiPSs). Such a multifunctional host effectively alleviates the polysulfides' shuttle and hence improves the performance of Li–S batteries.